Analogias utilizadas em fisiologia humana de alguns livros didáticos de biologia do ensino médio: análise crítica para seu uso pedagógico sistemático - Castro Júnior, Gumercindo Santos de (2019)
Starting from the assumption that the challenge of communication promotes the teachers a status and an ability to express and be understood as a communicator. Teachers may need to develop a way to engage the audience of students in their speech. The analogy is a resource used in argumentation especially in the science teaching area because this language tool can approximate known information of a new concept making it easy to build knowledge the one who is learning. This paper seeks to analyze the use of analogies into the content of human physiology in biology books distributed through Brazil’s national program of the didactic book (PNLD) to serve as a resource to improve the quality of education in the use of the didactic book in public schools of Brazil. Initially, the analog critical analysis inside the books was carried out by classifications proposed by Ferraz and Terrazzan. From this analysis, indicators were presented so that the teachers can use the analogy in a systematic and intentional way, applying the methodology of teaching with analogy (MECA), proposed by Nagem and collaborators, instead of using only spontaneously and automatically points of view. In this way, we analyzed 10 textbooks in which a sum of 33 analogies was identified. Those were distributed among contents of introduction to the study of physiology with an analogy, the digestive system with seven analogies, cardiovascular system, and immune system with three analogies each, urinary system and nervous system with six analogies each, the locomotive system with three analogies, the respiratory system only one analogy and endocrine system with three analogies. Although some authors use analogies to clarify the ideas and concepts addressed to the physiology and human anatomy, they don’t discuss that points systematically, nor do they discuss the deconstruction of these analogies, nor do they discuss the use of those analogies in the teacher’s guide inside the books, unless in two books collections of different authors, which emphasize the importance of the didactic resource analogies. According to the data obtained from the textbook’s analysis and academic productions of researchers dedicated to the theme analogies, it is possible to state that analogies approximate a known domain to an unknown domain constructed by using known analog and performing deconstruction from the last analogy, so that analog does not assume the domain position in the final analysis.